RELIGION AND VIOLENCE: TERRORISM AS A GLOBAL ISSUE - Rahayu, Ratih (Al-Masail: Journal of Islamic Studies, 2024)
This research aims to explore the phenomenon of terrorism and radicalism, as well as the factors underlying their spread. Using a qualitative approach, this research involved in-depth interviews with former members of terrorist groups, security practitioners, academics, and government officials. Ethnographic studies and content analyses of documents, social media, and propaganda materials were also conducted to understand the internal dynamics and communication strategies of terrorist groups. The results show that terrorist groups utilise social media and digital platforms to spread radical ideology and recruit new members through narratives that manipulate political, economic, and social issues. Preventing terrorism requires a comprehensive approach that involves international cooperation, education that emphasises human values and tolerance, and equitable economic development. Effective de-radicalisation programmes are also essential to help individuals affected by radical ideologies return to society. This research makes an important contribution in developing more effective prevention and counterterrorism strategies, by understanding the factors that drive terrorism and radicalism and identifying comprehensive prevention measures.